Deciphering Feasting in the Late Bronze Age Settlement of Rotbav, Transylvania. (22nd December 2017) - Dietrich, Laura; Bălăşescu, Adrian; Dietrich, Oliver
Abstract : In the present article we explore the possibilities of reconstructing social behaviour through a detailed analysis of the so-called 'ashmounds' of the Late Bronze Age in Eastern Europe, starting from new research at a settlement of the Noua culture, Rotbav in south-eastern Transylvania. For the first time, the excavations comprised not only the 'ashmound' but also its vicinity, revealing the existence of structures like houses and pits. Furthermore, the analysis and comparison of the finds revealed significant differences between the 'ashmound' and the rest of the domestic spaces. This leads us to a new interpretation of the 'ashmounds' as special places, linked with feasting activities and collective leatherworking. This new interpretation is supported not only by the examination of the finds but also by new archaeozoological and chemical analyses, which are usually missing in Eastern Europe. Abstract : Dans cet article nous explorons les possibilités de reconstruire le comportement social à travers l'examen détaillé des soi-disant « tertres de cendre » de l'âge du Bronze final en Europe de l'Est, sur la base de nouvelles recherches sur le site d'habitat de la culture de Noua à Rotbav en Transylvanie. Pour la première fois, les fouilles n'ont pas seulement ciblé les « amas de cendre » mais également leur périphérie, ce qui a documenté la présence de structures telles que des restes de maisons et des fosses. De plus, notre analyse comparative du mobilier révèle des différences importantes entre le « tertre de cendre » et le reste des espaces domestiques à Rotbav. Nous en dérivons une nouvelle lecture des « amas de cendre » en faveur d'endroits spéciaux liés aux festins et au travail collectif du cuir. Cette nouvelle interprétation s'appuie non seulement sur l'examen du mobilier mais aussi sur des analyses chimiques et archéozoologiques généralement peu appliquées en Europe de l'Est. Translation by Madeleine Hummler Abstract : Mit diesem Beitrag wird der Versuch unternommen prähistorische soziale Praktiken anhand einer detaillierten Untersuchung der sogenannten ‚Aschehügel' der späten Bronzezeit Osteuropas zu rekonstruieren, basierend auf neuen Untersuchungen in der Siedlung der Noua-Kultur von Rotbav in Südostsiebenbürgen. Zum ersten Mal ist hier nicht nur der ‚Aschehügel', sondern auch der ihn umgebende Bereich ausgegraben worden. Dort konnten Häuser und Gruben aufgedeckt werden. Eine vergleichende Untersuchung des Fundmaterials ergab signifikante Unterschiede zwischen ‚Aschehügel' und Siedlungsbereich. Diese Unterschiede führen zu einer Neuinterpretation der ‚Aschehügel' als spezielle, mit Festen und kollektiver Lederverarbeitung verbundene Plätze. Diese Interpretation wird nicht nur von Verteilung und Art der Funde gestützt, sondern auch von neuen archäozoologischen und chemischen Untersuchungen, die für viele osteuropäische Fundplätze bislang noch fehlen.